2011
DOI: 10.1007/s12223-011-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of fungal cell disruption—scope and limitations of the methods

Abstract: Simple and effective protocols of cell wall disruption were elaborated for tested fungal strains: Penicillium citrinum, Aspergillus fumigatus, Rhodotorula gracilis. Several techniques of cell wall disintegration were studied, including ultrasound disintegration, homogenization in bead mill, application of chemicals of various types, and osmotic shock. The release of proteins from fungal cells and the activity of a cytosolic enzyme, glucose-6-phosphate dehydrogenase, in the crude extracts were assayed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 52 publications
0
53
0
1
Order By: Relevance
“…We performed sonication with hourly time intervals and found that 3 h was the most effective sonication time for clotted blood (data not shown) that would be later macerated. This mechanical cell disruption may also effectively break the walls of some fungi (Klimek-Ochab et al, 2011). Although we did not standardize the volume of the clotted blood samples during sonication, we made sure that they were nearly identical.…”
Section: Discussionmentioning
confidence: 99%
“…We performed sonication with hourly time intervals and found that 3 h was the most effective sonication time for clotted blood (data not shown) that would be later macerated. This mechanical cell disruption may also effectively break the walls of some fungi (Klimek-Ochab et al, 2011). Although we did not standardize the volume of the clotted blood samples during sonication, we made sure that they were nearly identical.…”
Section: Discussionmentioning
confidence: 99%
“…19 The varying composition of the fungal cell wall leads to a range of tensile strengths, and there are a number of methods to break open the cell wall that vary in harshness. For the purposes of extracting DNA from both yeasts and filamentous fungi, mechanical disintegration has proven most effective 20 ; however, this method runs the risk of shearing the DNA and therefore must be carefully calibrated for the given sample composition.…”
Section: What Do We Know About the Lung Mycobiome?mentioning
confidence: 99%
“…The cytolysis of fission yeast in pellet (D) was confi rmed in cells treated with HNO 3 at concentration of 36% or above. Various cell disruption strategies have been used to develop an efficient, low-cost, and effective method for release of intracellular products (Middelberg, 1995;Geciova et al, 2002;Ho et al, 2008;Klimek-Ochab et al, 2011;Bzducha-Wróbel et al, 2014). Unfortunately, the method of cell wall digestion reported in previous studies to might be too expensive.…”
Section: Resultsmentioning
confidence: 99%